Redefining super recognition in the real world: Skilled face or person identity recognizers?. (18th March 2019) - Bate, Sarah; Portch, Emma; Mestry, Natalie; Bennetts, Rachel J.
Abstract : While there has been growing interest in the deployment of superior face recognizers in policing and security settings, it is likely that most real‐world tasks tap person rather than face recognition skills. We suggest that changes in real‐world screening tasks and terminology are required to distinguish these individuals from laboratory‐identified superior face recognizers, who have more potential in developing our theoretical understanding of the face recognition system.